Tuberculosis in biologic users for rheumatic diseases: results from the South African Biologics Registry (SABIO). Issue 2 (2nd December 2019) - Pettipher, Clive; Benitha, Romela
Abstract : Objectives: To evaluate the rate of tuberculosis (TB) in biologic users for rheumatic diseases in South Africa, the effectiveness of our latent TB infection (LTBI) programme, risk factors and outcome. Methods: TB cases were collected from the South African Biologics Registry (SABIO), rheumatologists and pharmaceutical companies. Demographics, LTBI screening and treatment, biological and disease modifying antirheumatic drug (DMARD) therapies, TB diagnosis and outcomes were recorded. Results: 96 TB cases were collected from 1999 to June 2017: rheumatoid arthritis 55, ankylosing spondylitis 27, psoriatic arthritis 4, and juvenile inflammatory arthritis 10. The TB rate was 1240/100 000 person years for biologic users (n=96) versus the biologic naive cohort of 0/100 000 years with an incidence rate difference of 0.0124 (p<0.0001). 60/96 had pulmonary and 36/96 had extra-pulmonary TB. Reactivation TB occurred in 45/96 cases. TB occurred in all biologics licenced in South Africa, the majority in monoclonal inhibitors (1683/100 000 person years) compared with etanercept (861/100 000 person years) and non-tumour necrosis factor (TNF) inhibitors (681/100 000 person years). The incidence rate ratio for monoclonal inhibitors compared with etanercept was 1.96 (p=0.005) and 2.47 (p=0.002) compared with non-TNF inhibitors with no significant difference between non-TNF inhibitors and etanercept (p=0.336). From those (12.9%) who screened LTBI positive, 14 developed TB, while the majority (77) screened LTBI negative. Black race, male sex, younger age and residence in the Western Cape were statistical risk factors. Two drug resistant TB cases and six deaths occurred. Conclusion: Reactivation and new onset TB is a significant risk for all biologics users in SA. Screening for LTBI is an imperative preventative strategy.